Torsional oscillation suppression-oriented torque compensate control for regenerative braking of electric powertrain based on mixed logic dynamic model. (1st May 2023) - Wang, Feng; Wu, Tonglie; Ni, Yiqing; Ye, Peng; Cai, Yingfeng; Guo, Jingang; Wang, Chuhai
Highlights: Gear backlash and shaft flexibility-considered dynamic model of regenerative braking. Mixed-logical dynamical hybrid model of driving mode to regenerative braking mode. Torsional oscillation suppression-oriented torque compensate control strategy. Abstract: This paper presents a novel torsional oscillation suppression-oriented torque compensate control for regenerative braking (TS-RTC) of electric powertrain, which is based on the gear-pair backlash and half-shaft flexibility-considered dynamic model of regenerative braking in electric powertrain (REP). According to the characteristics of transition from driving mode to regenerative braking mode (DM-to-RM), the dynamic models under different stages are transmitted into an equivalent mixed-logical dynamical (MLD) hybrid model. MLD-based hybrid braking system model and hybrid model predictive control are adopted to design the TS-RTC strategy, in which the torsional oscillation suppression-oriented cost function proved efficient in improving the regenerative braking performance during DM-to-RM process. Simulations and REP hardware in the loop test show that the fluctuation of half shaft torque are efficiently suppressed and the vehicle drivability is improved.